Retention rate of abatacept in rheumatoid arthritis patients in a real-life setting: results from a monocentric cohort - E. Molteni; C. Pirone; F. Ceccarelli; C. Castellani; C. Alessandri; M. Di Franco; V. Riccieri; F.R. Spinelli; R. Priori; R. Scrivo; F. Conti (PAGEPress Publications, 2024)
Objective. Data from trials demonstrated that abatacept (ABA) has a good safety and efficacy profile in treating rheumatoid arthritis. We have studied the retention rate of ABA in a real-life cohort of patients with rheumatoid arthritis. Methods. This is a monocentric, retrospective study including patients with rheumatoid arthritis classified by the American College of Rheumatology/European League Against Rheumatism 2010 criteria who started treatment with ABA. The Kaplan-Meier method was applied to evaluate the ABA retention rate. Results. This analysis was conducted on 161 patients [male/female 21/140, median age 65 years, interquartile range (IQR) 18.7, median disease duration 169 months, IQR 144.0]. 111 patients (68.9%) received ABA subcutaneously. ABA was associated with methotrexate in 61.9% of patients and was the first biological disease-modifying antirheumatic drug in 41%. We observed a median ABA survival of 66 months [95% confidence interval (CI) 57.3-74.7], with a retention rate of 88% at 6 months and 50.9% at 5 years. Drug survival was significantly higher in patients treated with ABA subcutaneously and in male patients (p=0.039 and p=0.018, respectively). Adjusted for main confounders, female gender was the main predictor of withdrawal (hazard ratio 5.1, 95% CI 1.2-21.3). Conclusions. Our study shows that better survival is associated with subcutaneous administration and male gender, confirming ABA effectiveness.